Human and mouse angiogenins: Emerging insights and potential opportunities - Sultana, Mst. Farzana; Abo, Hirohito; Kawashima, Hiroto (Frontiers in Microbiology, 2022)
Angiogenin, a well-known angiogenic factor, is crucial to the angiogenesis in gastrointestinal tumors. Human angiogenin has only one gene, whereas the murine angiogenin family has extended to incorporate six genes. Evolutionary studies have suggested functional variations among murine angiogenin paralogs, even though the three-dimensional structures of angiogenin proteins are remarkably similar. In addition to angiogenesis, the ubiquitous pattern of angiogenin expression suggests a variety of functions, such as tumorigenesis, neuroprotective, antimicrobial activity, and innate immunity. Here, we comprehensively reviewed studies on the structures and functions of human and mouse angiogenins. Understanding the structure and function of angiogenins from a broader perspective could facilitate future research related to development of novel therapeutics on its biological processes especially in gastrointestinal cancers.